การศึกษาการเตรียมโปรตีนไฮโดรไลเสต และกิจกรรมการต้านออกซิเดชันของเครื่องในปลาจากโรงงานอุตสาหกรรมแปรรูปสัตว์น้ำ - สุทธวัฒน์ เบญจกุล (มหาวิทยาลัยสงขลานครินทร์, 2024)
Production of protein hydrolysate from bigeye snapper (Priacanthus tayenus) viscera, a by-product from frozen surimi production industry, by enzymatic digestion and isolation and characterization of antioxidant peptides from bigeye snapper viscera hydrolysate were investigated. Protein hydrolysates were prepared by hydrolyzing defatted bigeye snapper viscera using flavourzyme (pH 7, 50oC), alcalase (pH 8, 50oC) or pepsin (pH 2, 37oC) at the enzyme concentration of 2.0 % (w/w, enzyme to viscera). It was found that the highest degree of hydrolysis (DH) of protein hydrolysate was observed in the flavourzyme digestion (22.26 % DH). DH of protein hydrolysate increased with increasing amount of flavourzyme concentration from 1.0% to 2.0% (p0.05). Protein hydrolysates of bigeye snapper viscera were prepared by using 2% of flavourzyme to obtain the DH of 5%, 10% and 20% and antioxidant activities including ABTS radical scavenging activity and ferric reducing antioxidant power (FRAP) as well as some protein functional properties were determined. It was found that antioxidant activities of bigeye snapper viscera hydrolysate increased with increasing of % DH. In addition, the hydrolysate of all DHs had protein solubility value above 95% over the pH range between 2 - 12. Emulsion activity index (EAI), emulsion stability index (ESI), foaming capacity and foaming stability of bigeye snapper viscera hydrolysate at all DHs tested were generally varied but all parameters tended to decrease with increasing pH. The isolation of antioxidant peptides from bigeye snapper viscera hydrolysate with 30% DH by using gel filtration chromatography with Sephadex G-25 resin found that peptide with the molecular weight between 275 Da to 14,791 Da exhibited the ABTS radical scavenging activity, whereas peptide fraction with molecular weight of 912 Da had highest antioxidant activity. The stability of the highest antioxidant activity peptide against pHs and heating was studied. It was noticed that ABTS radical scavenging activity of peptide fractions was not changed over the incubation at the pH range of 2-10 for 30 min (p>0.05) and over the heating at the temperature of 100 oC for 60 min. For the heating at 121 oC, antioxidant activity was not changed at the first 30 min (p>0.05) but with further the heating time to 60 min the antioxidant activity was increased (p<0.05). Isolation of antioxidant peptides from bigeye snapper viscera hydrolysate with 30% DH was performed by using membrane ultrafiltration with the molecular weight cut off (MWCO) of 1 and 3 kDa. It was observed that peptide fraction with molecular weight between 1-3 kDa (fraction II) and peptide fraction with molecular weight lower than 1 kDa (fraction III) had ABTS radical scavenging activity, metal chelating activity and hydroxyl radical scavenging activity higher than the peptide fraction with molecular weight higher than 3 kDa (fraction I). This study showed that bigeye snapper viscera could be used as a raw material for the production of good antioxidant peptides by enzymatic digestion process and the peptides could be applied in various foods and other products due to the high stability of peptides against the processing conditions as well as their adequate functional properties.